Reassessing Nation-Branding: Danish Public Diplomacy towards Muslim-Majority Countries after the 2005 Cartoon Crisis - Dharmaputra, Radityo (Global Strategis, 2017)
This article reassesses Danish efforts of nation-branding towards Muslim-majority countries after the 2005 Prophet Cartoon Crisis. It disputes Rasmussen &Merkelsen’s (2012) findings regarding the shifting Danish policy to a more brand-conscious policy. This article differentiates reactive crisis diplomacy and a brand-informed policy and finds that Danish policy towards Muslim-majority countries was closer to the principle of reactive crisis diplomacy, rather than a conscious nation-branding. Result from this research could be used as the basis for future research on the idea that nation branding could complement the use of classic diplomacy. As the Danish case has shown, the lack of coordination between governmental and non-governmental actors and the lack of conscious effort on nation branding could negate the possibility of creating a good brand image.